2016
DOI: 10.1016/j.jbtep.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

“What I believe is true”: Belief-confirming reasoning bias in social anxiety disorder

Abstract: SAD patients showed concern-congruent belief biased interference effects when judging the logical validity of social anxiety relevant syllogisms. Such concern-relevant belief bias may contribute to the persistence of anxiogenic beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…For socially anxious individuals, this becomes even more pressing: Although HSAs’ core fear entails expectation of inevitable rejection, it seems as if they “secretly abandon” any thought about how to handle true rejection. This seems in line with cognitive models of SAD (e.g., Rapee and Heimberg, 1997) as well as research suggesting that HSAs may preferentially process belief-confirming above belief-disconfirming information (Belief-bias; Vroling et al, 2016). In addition, it may be the case that while HSAs have a whole repertoire of emotions and strategies available to try and manage their fears and prevent their utmost nightmare to become true, they do not know how to behave once rejection does indeed occur.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For socially anxious individuals, this becomes even more pressing: Although HSAs’ core fear entails expectation of inevitable rejection, it seems as if they “secretly abandon” any thought about how to handle true rejection. This seems in line with cognitive models of SAD (e.g., Rapee and Heimberg, 1997) as well as research suggesting that HSAs may preferentially process belief-confirming above belief-disconfirming information (Belief-bias; Vroling et al, 2016). In addition, it may be the case that while HSAs have a whole repertoire of emotions and strategies available to try and manage their fears and prevent their utmost nightmare to become true, they do not know how to behave once rejection does indeed occur.…”
Section: Discussionsupporting
confidence: 88%
“…In Mallott et al (2009), HSAs showed the signs of avoidance such as decreased eye contact after rejection and giving others less reward than non-anxious controls. In fact, these findings are in line with cognitive theories Clark and Wells, 1995; Rapee and Heimberg, 1997) as well as with a theoretical framework suggesting that HSAs tend to preferentially process belief-confirming above belief-disconfirming information (Belief-bias; Vroling et al, 2016). This implies that HSAs would experience explicit or putative rejection as confirmation of their initial beliefs and fears, strengthening them even further, and deem any action to countervail the rejection pointless (Clark and McManus, 2002; Hofmann and DiBartolo, 2010).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In daily life, individuals with social anxiety are more likely to be alone than to interact with others, which greatly reduces their opportunities to engage in prosocial behaviors. Vroling et al found that with increasing levels of social anxiety, the reward felt by rejected individuals would decrease and would lead to a stronger avoidance tendency [ 26 ]. Thus, individuals with social anxiety may exhibit decreased levels of prosocial behaviors following explicit exclusion and avoidance tendencies [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…If one takes time to reflect on one’s thoughts with logic and rational analysis, then another type of mental processing will be included in one’s emotional reflection ( Yang and Mattila, 2020 ). That is, individuals’ reflective reasoning can affect their emotion (e.g., social anxiety) and raise social conformity during social interaction ( Vroling et al, 2016 ). Furthermore, according to the I’m OK, You’re OK theory ( Harris, 2004 ), there are two factors which influence knowledge sharing: opportunistic and self-interested thinking ( Estrada et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%